Sakinah Resilien dalam Qs. Ar-Rum [30]:21: Rekonstruksi Makna Keluarga Sakinah Melalui Pendekatan Tafsir Maqāṣidi - Fadwa Nabilah; Ahmad Nurrohim (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2026)
The phenomenon of the modern domestic crisis, triggered by digital disruption, shifting social roles, and increasing mental health vulnerabilities, calls for a reorientation in our understanding of the concept of sakinah. Traditional interpretations, which tend to define sakinah as a descriptive state of tranquillity, often fall short in addressing the dynamics of contemporary relational conflicts. This study aims to reconstruct the meaning of sakinah in QS. Ar-Rūm [30]: 21 through a maqāṣidi exegetical approach. The method employed is a literature review with qualitative analysis of exegetical texts and the modern social context. The findings indicate that sakinah is not merely understood as emotional tranquillity, but as a relational mechanism that serves to preserve the stability of the soul (ḥifẓ al-nafs) and the continuity of the lineage (ḥifẓ al-nasl). This study proposes the concept of resilient sakinah, namely the interpretation of sakinah as an adaptive capacity in managing conflict in a ma‘rūf manner. Thus, sakinah is not measured by the absence of conflict, but by the ability to maintain relationships oriented towards the common good.